Recommendation System for Cross-Platform Mobile Development Framework - dos Santos, Denisson Santana; Nunes, Hugo Dória; Macedo, Hendrik Teixeira; Neto, Alberto Costa (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Mobile application developers, aimming to make their applications available to the largest number of platforms, are increasingly seeking to optimize how to develop mobile applications. Creating the same specific application for each platform demands greater financial, time and labor investment. In order to reduce these problems, mobile development frameworks for multiplatforms have emerged, making possible to create multi-platform applications from the same source code. However, a new issue arises for the developer - the plurality and diversity of these frameworks, each one with objectives and characteristics that sometimes make them closer and in other cases farther. In addition, there is a demand for multi-purpose applications and work teams with different training profiles. For these reasons, choosing a framework is not trivial. This paper presents an approach that indicates which multi-platform application development framework is most suitable for a given project, implemented as a knowledge-based recommendation system that considered the critical factors of a given project.